The music of James Horner. - Horner, James (Silva Screen Records, 2011)
From Titanic to Avatar, Academy Award winning composer James Horner has been responsible for some of the most memorable music to be heard on the big screen. Here the City of Prague Philharmonic Orchestra performs highlights from Horner's acclaimed career including music from Ransom; Apollo 13; The Mask of Zorro; and Braveheart.